Acute malnutrition relapse and associated factors among 6–59 months old children treated in the community-based management of acute malnutrition in Dessie, Kombolcha, and Haik towns, Northeast Ethiopia - Yitayew, Yibeltal Asmamaw; Yalew, Zemen Mengesha; Nebiyu, Samuel; Jember, Desalegn Abebaw (Frontiers in Public Health, 2024)
Introduction: Undernutrition is a major health concern in many developing countries, and it is one of the main health problems affecting children in Ethiopia. Although many children experience multiple relapses following the management of severe acute malnutrition, it is scarcely studied in Ethiopia.: A community-based cross-sectional study was conducted in Dessie, Kombolcha, and Haik towns among 6-59-month-old children enrolled in and discharged from communitybased acute malnutrition management (CMAM). The total sample size was 318 children, and the data were collectedion was conducted from April 15, 2021, to May 14, 2021. The data were entered into EPI data version 4.4.1 before being exported and analyzed with SPSS version 25 software. A multivariate logistic regression analysis was performed, and a 95% confidence interval and p-value <0.05 were used to identify significantly associated variables. Additionally, the weight-for-height z-score anthropometric indices (WHZ) wasere generated using the WHO Anthro 3.2.2 software.The overall acute malnutrition relapse after discharge from CMAM was 35.2% (6.6% relapsed to severe acute malnutrition and 28.6% relapsed to moderate acute malnutrition).The following variables were significantly associated with the relapse of acute malnutrition: